Formulation of Decaffeinated Instant Coffee Effervescent Tablet - Andi dharmawan; Sukrisno Widyotomo; Hendy Firmanto; Bayu Setyo Abdurizal (Indonesian Coffee and Cocoa Research Institute, 2016)
Decaffeinated coffee is an alternative for caffeine intollerant consumer as a safe and practical choice. However, since decaffeination process employ high temperature extraction, the coffee produced usually possesses inferior sensory qualities. This research was aimed to get an optimum formulation of effervescent coffee tablet that has good physical and sensory quality. In this research, effervescent coffee tablet was formulated with three different ratios of the decaffeinated instant coffee and effervescent reagent (citric acid and sodium bicarbonate), namely 1.5:1; 1:1; and 1:1.5 (w/w) weighed in 3 g per tablet serving. Sensory evaluation was carried out organoleptically in several criteria such as flavors, aromas, and colors on 40 mL, 80 mL, and 120 mL of the solution. Futher, physical quality evaluation was done by measuring its weight uniformity, hardness, friability, and run time which then calculated by statistic analytical method to decide the best formulation. Based on the result, the best formulation of effervescent coffee tablet was 1:1.5 (w/w) due to its shortest run time (4.2 minutes), good weight uniformity and hardness value, 1.16 ± 0.03 g/cm3 dan 6.7 ± 0.5 kg, respectively, while friability value was the smallest (2%) compared to other formulations. The brewing of this formulation in 40 mL water also had best sensory profiles in term of aroma, color and flavor.